Mastering SAP S/4HANA 1709 – Strategies for Implementation and Migration : Transition to S/4HANA with tried and tested deployment scenarios /: Transition to S/4HANA with tried and tested deployment scenarios. (2018) - Gupta, Nitin
No abstract available